The Upper Ordovician fauna of Frobisher bay, Baffin Land - Roy, Sharat Kumar, 1897-1962. (Chicago : [s.n.], 1941)
"The Data and material upon which this paper is based were collected by me during the seasons of 1927 and 1928, while I was serving as geologist of the Rawson-MacMillan expedition of the Field museum to Labrador and Baffin Land." - Pref. Boundwith: The vertebrate fauna of the Selma Formation of Alabama, pts. 1-6. Bibliography: p.198-205. Mode of access: Internet.